Using ICD for structural analysis of clusters: a case study on NeAr clusters - Faßhauer, Elke; Förstel, M.; Pallmann, Sebastian; Pernpointner, Markus; Hergenhahn, U. (New journal of physics, 2014)
We present a method to utilize interatomic Coulombic decay (ICD) to retrieve information about the mean geometric structures of heteronuclear clusters. It is based on observation and modelling of competing ICD channels, which involve the same initial vacancy, but energetically different final states with vacancies in different components of the cluster. Using binary rare gas clusters of Ne and Ar as an example, we measure the relative intensity of ICD into (Ne+)2 and Ne+Ar+ final states with spectroscopically well separated ICD peaks. We compare in detail the experimental ratios of the Ne-Ne and Ne-Ar ICD contributions and their positions and widths to values calculated for a diverse set of possible structures. We conclude that NeAr clusters exhibit a core-shell structure with an argon core surrounded by complete neon shells and, possibly, further an incomplete shell of neon atoms for the experimental conditions investigated. Our analysis allows one to differentiate between clusters of similar size and stochiometric Ar content, but different internal structure. We find evidence for ICD of Ne 2s−1, producing Ar+ vacancies in the second coordination shell of the initial site.
Gesehen am 07.07.2020